GE_GERICHTE C/6174/2014 vom 30. Januar 2017 - GE Cour de justice (2017)
DÉFAUT DE LA CHOSE ; RÉDUCTION(EN GÉNÉRAL) ; DROIT D'ÊTRE ENTENDU ; CONSIGNATION EN JUSTICE | CPC.316.3; CO.256.1; CO.259.a; CO.259.d; CO.259.g.1; CPC.53; Cst.29.2;